Comparison of cardiovascular responses between remifentanil and fentanyl on laryngoscopy and tracheal intubation in patients undergoing elective surgery. - Lai SC,; Choy YC, (Department of Surgery, UKM Medical Centre, 2014)
This was a prospective, randomized, double-blind study comparing the effect of remifentanil and fentanyl on cardiovascular responses from laryngoscopy and tracheal intubation. Forty-four ASA I or II patients aged between 18-65 yrs scheduled for elective surgery under general anaesthesia, were recruited and randomized into two groups. Each patient in Group R received remifentanil of 0.5 mcg/kg bolus over 30 seconds followed by an infusion of 0.25 mcg/kg/min and each patient in Group F received fentanyl of 2 mcg/kg bolus over 30 seconds followed by an infusion of normal saline. Anaesthesia was then induced with propofol, rocuronium and 2% sevoflurane with 100% oxygen. Cardiovascular changes were recorded every minute for 3 minutes after induction and 5 minutes after tracheal intubation. The heart rate remained stable throughout the induction and intubation period in both groups. None of the patients in the remifentanil group develop bradycardia. Systolic blood pressure (SBP) and mean arterial pressure (MAP) were significantly lower in the fentanyl group at the 3rd minute post-induction and 5th minute post-intubation (p < 0.05). Diastolic blood pressure (DBP) in the fentanyl group was significantly lower at the 2nd and 3rd minute post-induction and 4th and 5th minute post-intubation (p < 0.05). The blood pressure remained stable for the remifentanil group throughout the induction and intubation period. Six patients (27.2%) in the fentanyl group and one patient (4.5%) in the remifentanil group experienced hypertension. Three patients (13.7%) from each group experienced hypotensive episodes. In conclusion, remifentanil 0.5 mcg/kg bolus followed by 0.25 mcg/kg/min infusion resulted in SBP, MAP and DBP remained slightly lower than baseline throughout the whole period but still consider stable, as these changes were not statistically significant.